Longitudinal ozone exposure and SARS-CoV-2 infection in late pregnancy: a retrospective cohort study - Zhang, Lin; Tian, Jiaqi; Duan, Shuyin (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAtmospheric ozone is a common air pollutant with known impacts on maternal and fetal health. However, the relationship between gestational ozone exposure and susceptibility to respirovirus infection remains unclear. This study aims to assess the association between longitudinal ozone exposure during pregnancy and COVID-19 risk in late gestation.MethodsThis retrospective cohort study included 600 pregnant women (300 infected with SARS-CoV-2 and 300 uninfected) who delivered at one hospital in Jinan, China from November 2022 to January 2023. Individual ozone exposure levels throughout gestation were estimated based on local ambient monitoring data. Logistic regression models were constructed to examine the association between gestational ozone exposure and COVID-19 status in late pregnancy, adjusting for demographic and clinical variables.ResultsIn Jinan, ozone levels increased by 1.85 ppb annually and peaked between April and October, corresponding to winds from the south and southwest. Higher ozone exposure over pregnancy was associated with lower odds of SARS-CoV-2 infection in late gestation (OR per IQR increase = 0.60, 95% CI: 0.40-0.90). Compared to the lowest quartile (reference), the highest ozone quartile corresponded to a 99% decreased infection risk (OR = 0.01, 95% CI: 0.00-0.03). Increased maternal age and pre-pregnancy BMI were associated with higher COVID-19 risk.ConclusionsLongitudinal ozone exposure during gestation may be protective against SARS-CoV-2 infection in late pregnancy. Further studies are needed to confirm this finding and elucidate underlying mechanisms. These results highlight the potential importance of environmental exposures in COVID-19 susceptibility.